Biblical theology and/or theological interpretation of scripture?: Defining the relationship - Treier, Daniel J. (Scottish journal of theology, 2008)
‘Biblical theology’ has long influenced modern theological method, especially Protestant, as both boon and bane. Its role has been seen as either pivotal or problematic in the attempt to construe the Christian Bible as scripture with unified teaching for the contemporary church. The attempt to unfold biblical teaching as having organic unity, related to an internal structure of theological concepts, is frequently perceived as a failure, a has-been that leaves us only with fragmentation – between parts of the Bible, between academy and church, church and world, clergy and laity, and between various theological disciplines. Today a new movement is afoot, often labelled ‘theological interpretation of scripture’. Some of its adherents define this practice as distinct from, even opposed to, biblical theology. Others treat the two practices as virtually coterminous, while perhaps contesting what ‘biblical theology’ is typically taken to be in favour of new theological hermeneutics. Much of the difficulty in defining the relationship, then, stems from lingering debates about what biblical theology can or should be. The rest of the difficulty is perhaps rooted in the dilemma of any interdisciplinary efforts: how to breach unhelpful sections of disciplinary boundaries without redefining territory so nebulously that no one knows where they are.